2007
DOI: 10.1080/14768320701372018
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant women's third trimester exercise behaviors, body mass index, and pregnancy outcomes

Abstract: Pregnancy and postpartum are determinants of sedentary and low active lifestyles. Before effective physical activity interventions are implemented within this population, it is necessary to prospectively examine, during each trimester, their exercise determinants and behaviors within a theoretical framework. The purposes of this study were to: (a) prospectively examine women's third trimester exercise intention and behavior using the theory of planned behavior (TPB), and (b) examine group differences across th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“… 29 30 31 32 Overall, the studies were of moderate (28 studies, 51.9%) 29 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 or good (21 studies, 38.9%) 30 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 methodological quality, while 5 studies (9.2%) were classified as of poor methodological quality. 78 79 80 81 82 Most studies were conducted in a community setting (59.3%) and included low-risk, predominantly Caucasian women. Characteristics of the studies are summarized in Table 1 , while detailed descriptions of exposures and outcomes of individual studies can be found in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 29 30 31 32 Overall, the studies were of moderate (28 studies, 51.9%) 29 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 or good (21 studies, 38.9%) 30 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 methodological quality, while 5 studies (9.2%) were classified as of poor methodological quality. 78 79 80 81 82 Most studies were conducted in a community setting (59.3%) and included low-risk, predominantly Caucasian women. Characteristics of the studies are summarized in Table 1 , while detailed descriptions of exposures and outcomes of individual studies can be found in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“… 75 Most studies defined birth weight outcomes as prespecified in the protocol, with a few exceptions using close definitions. 38 49 51 53 55 61 65 72 73 79 81…”
Section: Resultsmentioning
confidence: 99%
“…TPB is most often used in the context of health behaviors such as smoking (Burkhalter, Warren, Shuk, Primavera, & Ostroff, 2009), exercising (Downs & Hausenblas, 2007), and consuming alcohol (Zimmermann & Sieverding, 2010). It has also been used to examine self-harm and suicide with promising results.…”
mentioning
confidence: 99%
“…16,[24][25][26] However it should be noted that these women did not deliver "low birth weight" infants. Low birth weight is considered to be infants who weigh less than 2500 g at birth; 6 infants in these studies had healthy birth weights ranging from 2700-4000 g. 1 Lastly, although physical activity during pregnancy may aid in controlling excessive postpartum weight retention, 27 intervention trials with aims of promoting physical activity and appropriate energy intakes to reduce postpartum weight retention have proven both successful 28 and unsuccessful. 29 Energy intakes during pregnancy impact gestational weight gain and infant birth weight.…”
mentioning
confidence: 99%